2019
DOI: 10.1108/lm-09-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

Leadership style as a predictor of employee commitment in university libraries in South-West, Nigeria

Abstract: Purpose The purpose of this paper is to investigate the influence of leadership style (LS) on employee commitment (EC) in university libraries in South-West, Nigeria. Design/methodology/approach The study adopted a survey research design. The population of the study consisted of 684 librarians from 43 universities in the six states of South-West, Nigeria. A validated questionnaire was used for data collection. Data were analyzed using descriptive and inferential statistics. Findings Findings showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Libraries operate effectively when their employees are committed to the principles, ethics and objectives of the library (Mayowa-Adebara and Opeke, 2019). Conversely, the performance of a library is diminished when the level of commitment of its employees is low and, as a result, the employees simply put in the minimum performance needed to maintain their employment (Akinyemi and Ifijeh, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Libraries operate effectively when their employees are committed to the principles, ethics and objectives of the library (Mayowa-Adebara and Opeke, 2019). Conversely, the performance of a library is diminished when the level of commitment of its employees is low and, as a result, the employees simply put in the minimum performance needed to maintain their employment (Akinyemi and Ifijeh, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Absorbing these pressures requires a high level of employee commitment. Employee commitment is among the main work attitudes investigated by scholars in librarianship in the contemporary era, in which the demand for quality services from libraries is increasing perpetually (Banji, 2020; Mayowa-Adebara, 2018). The literature has revealed that employee commitment is a key determinant of the success or failure of a library (Ogunbanjo, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include examining the consequences of TL, such as developing a shared organisational vision, developing models for implementing goals, collaboration, emotional motivation or assessing its effect on the staff's performance. Several previous studies in LIS have also examined the role of TL in the librarians' performance [66][67][68][69]. Few studies have also addressed assessing the effect of this type of leadership on KM in libraries [9].…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…LIS researchers in the field of Human Resource Management believe that committed librarians have a strong belief in the goals of their profession. They consciously strive to develop their professional standards to promote the profession by accepting the organisational goals [69,77]. These librarians are highly enthusiastic to enhance their skills and specialised knowledge by attending in-service training courses and scientific meetings related to the profession.…”
Section: Literature Reviewmentioning
confidence: 99%